Three Two‐Dimensional Approaches for Simulating the Water Flow Dynamics in a Heterogeneous Tile‐Drained Agricultural Field in Denmark. Issue 6 (13th December 2018) - Varvaris, Ioannis; Børgesen, Christen Duus; Kjærgaard, Charlotte; Iversen, Bo V.
Abstract : Core Ideas: Simulating water flow dynamics in a clayey subsurface drained agricultural field. Three two‐dimensional models incorporating preferential water flow were used. All models produced a reasonably good fit to the hydrograph features. Examine models' capabilities and weaknesses for simulating the drainage dynamics. Non‐equilibrium preferential flow has received increasing attention in modeling water flow dynamics across tile‐drained agricultural fields. The HYDRUS‐2D software package was used in this study to generate a hydrogeological model for simulating the water flow dynamics across hydro‐topographical gradients and drainage sequences at drainage subcatchment (western part of Norsminde catchment in Denmark). The selected study area is characterized by spatial variability in the geological, stratified heterogeneity. Three two‐dimensional models incorporating preferential water flow were used to examine the ability of each approach to predict the drainage dynamics and water balance in a clayey subsurface drained agricultural field: (i) a single‐porosity model, (ii) a dual‐porosity model, and (iii) a dual‐permeability model. The initial parameterization of the models relied on in situ observations of soil structure, soil hydraulic property maps of Denmark and pedotransfer functions. The models, once calibrated against observed drainage data, were used for the reproduction of the subsurface drainage water dynamics for different time periods for the specific agricultural landscape. The different conceptual approaches gave a fairly good fit to the hydrograph features for both the calibration and validation datasets. The predictive ability of all models for the calibration dataset was fairly similar, while for the first and second validation datasets better results were obtained with the dual‐porosity and dual‐permeability models, respectively. The calibrated values of the effective parameters had been examined using laboratory data and in situ measurements of the groundwater level to evaluate how well these parameters physically represent the flow domain.